Systematic review of interventions aimed at improving HIV adherence to care in low- and middle-income countries in Sub-Saharan Africa - Laura E. Pugh; Jacob S. Roberts; Nikita Viswasam; Elizabeth Hahn; Sophia Ryan; Ghilane Turpin; Carrie E. Lyons; Stefan Baral; Bhakti Hansoti (Elsevier, 2022)
Long-term adherence to antiretroviral medication continues to present as a challenge along the continuum of the HIV care cascade. HIV interventions and support programs are significantly threatened in resource-limited settings by challenges in maintaining long-term follow-up for ART adherence. We sought to complete a systematic review to comprehensively examine ART adherence and retention in care interventions in Sub-Saharan Africa and to report on the implementation of interventions in real-world settings to inform future health investments in HIV care. Interventions were grouped according to their impact on individual, community, and health-systems levels. While a vast majority of studies evaluated a combination of interventions, those studies that incorporated the community as a resource were most successful. In addition, providing education and behavior reminders proved effective and should be accompanied by community and peer efforts for best results. Multi-level interventions, such as combining individual and community-level interventions showed promising results for long term ART adherence.